Kerangka Hukum Keberhasilan Good Corporate Governance Layanan dan Proses Pemerintahan dan Perusahaan di Finlandia - Chandra Erick Manaek Pandapotan Lumban Gaol; Elisantris Gultom; Kardoman Tumangger (Fakultas Hukum, Universitas Warmadewa, 2025)
Good governance, both corporate and public, is a crucial foundation for legitimacy, accountability, efficiency, public trust, and a nation's sustainable development. Finland is widely known as a country with leading governance practices. However, juridical analysis that comprehensively integrates the legal framework of corporate GCG and public governance within a single national legal system like Finland's is still rarely found in the literature. This research aims to deeply and systematically analyze the formal legal and soft law frameworks that shape, regulate, and enforce the principles of corporate and public governance in Finland. Using a normative legal research method with statutory, conceptual, and institutional approaches, this study examines primary Finnish legal sources and relevant literature. Main findings indicate Finland possesses a robust and layered governance legal architecture. Corporate GCG is governed by the Companies Act and reinforced by the Finnish CG Code (comply or explain principle), emphasizing transparency and board accountability. Public governance is based on the Constitution and strong administrative law (Administrative Procedure Act, Act on Openness), upholding legality, public service, and transparency, overseen by independent bodies like the Ombudsman. A strong emphasis on ethics and integrity cuts across both sectors. As a result, Finland's legal framework demonstrates coherence and a strong commitment to implementing good governance principles in private and public spheres, creating a mutually reinforcing, trustworthy governance ecosystem that offers valuable insights for other countries.